Comparing Intraoral Radiography and Computed Tomography for Detecting Radiographic Signs of Periodontitis and Endodontic Disease in Dogs: An Agreement Study - Campbell, Robert D.; Peralta, Santiago; Fiani, Nadine; Scrivani, Peter V. (Frontiers in Veterinary Science, 2016)
Objective: To determine whether computed tomography and intraoral radiography are interchangeable for detecting signs of periodontitis and endodontic disease in dogs. Materials and Methods: An agreement study was performed using 40 dogs that previously underwent intraoral radiography and computed tomography during the same anesthetic episode. Images of each tooth were examined by two blinded observers for signs of periodontitis and/or endodontic disease. Agreement between imaging modalities and between observers was assessed using the Kappa statistic. Results: Agreement between modalities for detecting periodontitis in the maxillae ranged from poor to very good (κ 0.07-1.00) with 16/20 (80%) of the teeth having a score of moderate or better (κ ≥ 0.41). Agreement between modalities for detecting signs consistent with periodontitis in the mandibles ranged from poor to very good (κ 0.01-1.00) with 10/22 (45%) of the teeth having a score of good or better (κ ≥0.61); 50% of the disagreement was present in the incisors. Agreement between modalities for detecting signs consistent with endodontic disease in the whole mouth ranged from fair to very good (κ 0.21-1.00) with 30/42 (71%) of the teeth having a score of moderate or better (κ ≥0.41). Agreement between observers evaluating IOR ranged from poor to very good (κ 0.05-1) for detecting signs consistent with periodontitis and from fair to very good (κ 0.36-1) for detecting signs consistent with endodontic disease, in the whole mouth. Agreement between observers evaluating CT ranged from fair to very good (κ 0.35-1) for detecting signs consistent with periodontitis and from fair to very good (κ 0.36-1) for detecting signs consistent with endodontic disease, in the whole mouth Conclusions: Performing both computed tomography and intraoral radiography may be unnecessary to detect signs consistent with periodontitis and endodontic disease in dogs based on the amount of agreement between modalities and observers when CT images are acquired and reconstructed in 0.5 or 1 mm slice thickness, except for diagnosing periodontitis in the mandibular incisors.